The pirateology handbook : a course in pirate hunting - Lubber, William; Steer, Dugald; Twist, Clint; Andrew, Ian P., 1962- (Cambridge, Mass. : Candlewick Press, 2008)
A handbook written by the fictional captain William Lubber describes what life was like for pirates in the 1800s, including the duties of the crew, weapons and tools, kinds of ships, where they sailed, punishments, and famous real pirates.
Keywords: Pirates